Manufacturing method of fluorescent magnetic particles for wet magnetic particle testing

By controlling the proportions of magnetic powder, water-soluble resin, and fluorescent pigment, and employing granulation and re-granulation, the method ensures the fluorescent pigment remains attached, enhancing detection sensitivity and clarity of defect indication patterns in fluorescent magnetic powder liquids.

JP7612442B2Active Publication Date: 2025-01-14MARKTEC CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021018952
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-02-09
Publication Date
2025-01-14
Estimated Expiration
2041-02-09

AI Technical Summary

Technical Problem

Existing methods for producing fluorescent magnetic powder result in the fluorescent pigment peeling off or falling off during use, leading to reduced detection sensitivity due to background phenomena and unclear defect indication patterns.

Method used

A method involving specific proportions of magnetic powder, water-soluble resin, and fluorescent pigment, followed by granulation and re-granulation processes, ensures the fluorescent pigment remains firmly attached to the magnetic powder particles, reducing peeling and falling off.

Benefits of technology

The method produces a fluorescent magnetic powder liquid with high detection sensitivity, capable of clearly distinguishing defective areas from non-defective areas, even detecting minute defects directly under the surface.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007612442000004
    Figure 0007612442000004
  • Figure 0007612442000005
    Figure 0007612442000005
  • Figure 0007612442000001
    Figure 0007612442000001
Patent Text Reader

Abstract

To provide fluorescent magnetic powder for wet magnetic powder flaw detection test that is obtained by coating, with water-soluble resin, a surface of a composite particle obtained by attaching fluorescent pigment to a surface of a magnetic powder particle with water-soluble resin therebetween, in which the fluorescent pigment is hardly peeled off and falls off in fluorescent magnetic powder liquid and during a flaw detection test, a background phenomenon hardly occurs, and the fluorescent pigment remains on the surface of the magnetic powder particle at a high ratio, and thus fluorescent magnetic powder liquid can be manufactured which can obtain a clear defect indication pattern with the remarkable difference between a defective part and a part other than the defective part.SOLUTION: A method for manufacturing fluorescent magnetic powder for wet magnetic powder flaw detection test includes: granulating a mixture containing 20 weight%-40 weight% of magnetic powder having a median diameter of 2 μm-7 μm, 5 weight%-12 weight% of water-soluble resin-containing emulsion having a glass transition temperature of 10°C or less, 5 weight%-25 weight% of fluorescent pigment, and water; dispersing 10 weight% or more-55 weight% of the granulated particles in an aqueous solution containing 5 weight-35 weight% of the water-soluble resin-containing emulsion; and subsequently performing granulation again to manufacture the fluorescent magnetic powder for wet magnetic powder flaw detection test.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing fluorescent magnetic powder for wet magnetic particle testing. In particular, the fluorescent magnetic powder produced by the present invention is a fluorescent magnetic powder obtained by coating the surface of a composite particle, in which a fluorescent pigment is attached to the surface of a magnetic powder particle via a water-soluble resin, with a water-soluble resin. Therefore, the fluorescent pigment is unlikely to peel off or fall off in the fluorescent magnetic powder liquid or during a flaw detection test. Therefore, the background phenomenon caused by the peeled or fallen fluorescent pigment is unlikely to occur, and a large proportion of the fluorescent pigment remains on the surface of the magnetic powder particles, resulting in a clear defect indication pattern. This is a method for producing fluorescent magnetic powder for wet magnetic particle testing that can produce a fluorescent magnetic powder liquid that can detect fine open defects and non-open defects just below the surface with high detection sensitivity. [Background technology]

[0002] As is well known, the wet magnetic particle testing method is standardized in JIS-Z-2320, and this test method involves applying commercially available magnetic powder for wet magnetic particle testing (conductive magnetic particles such as iron tetraoxide particles or pure iron particles to which fluorescent pigments such as Lumogen Yellow S0790 (manufactured by BASF) or Festa A (manufactured by Swada) are attached using a synthetic resin binder such as a cellulose acetate synthetic resin or a vinyl butyral synthetic resin) with an average particle diameter of 3 to 30 μm (volume-based distribution display, the same applies below), and a true specific gravity of 2 to 5 g / cm to a magnetized test object, for example, steel parts such as shafts, steel materials such as magnetic bodies and billets, magnetic bodies, etc. 3 This is a test method in which a magnetic powder liquid prepared by dispersing a powder of the above material (hereinafter referred to as "magnetic powder") in water is applied to the open defect portion of the test object (microscopic cracks or pinholes present on or near the surface of the test object) by causing the magnetic powder dispersed in the magnetic powder liquid to gather and form a defect indication pattern, and the open defect portion is detected using this defect indication pattern (hereinafter this test method is referred to as "wet magnetic particle testing").

[0003] There are two methods for producing magnetic powder: one known to those skilled in the art as the "pulverization method" and the other known as the "atomization method."

[0004] The grinding method is a method in which a fluorescent pigment is dispersed in a solution obtained by dissolving an organic solvent-soluble synthetic resin as a binder in a volatile organic solvent, and then magnetic powder is mixed and kneaded to form a paste-like substance. The paste-like substance is then dried to form a mass, which is then ground into fine particles using a grinding machine such as a ball mill, and classified using a sieve or the like to obtain fluorescent magnetic powder of the desired particle size.

[0005] The spray method is a method in which magnetic powder, fluorescent pigment, and a binder consisting of a water-dispersible or water-soluble synthetic resin are added to water to form a paste, and the paste is then sprayed or scattered into the air using a spray nozzle or centrifugal disk, followed by drying and granulation, to obtain spherical fluorescent magnetic powder of the desired particle size in which the magnetic powder and fluorescent pigment are attached via the synthetic resin.

[0006] Fluorescent magnetic powder is dispersed in a dispersion liquid such as water to prepare a fluorescent magnetic powder liquid. However, if the fluorescent pigment peels off or falls off from the surface of the magnetic powder particles in the fluorescent magnetic powder liquid or during flaw detection testing, the peeled off or fallen off fluorescent pigment will adhere to the surface of the test object other than the defective area and emit fluorescence, making it difficult to see the defect indication pattern. This is known as the background phenomenon, and there is a problem in that the detection sensitivity of the defective area is reduced.

[0007] Furthermore, when the fluorescent pigment peels off or falls off, the amount of fluorescent pigment covering the surfaces of the magnetic powder particles decreases, resulting in a decrease in the brightness of the defect indication pattern and a decrease in the detection sensitivity of defective portions.

[0008] Therefore, there is a need to develop a fluorescent magnetic powder that can be used to create a fluorescent magnetic powder liquid with high detection sensitivity in which the fluorescent pigment adheres firmly to the surface of the magnetic powder particles and is not easily peeled off or fallen off in the fluorescent magnetic powder liquid or during flaw detection testing, making it less likely to cause background phenomena, and in which a high proportion of the fluorescent pigment covering the surface of the magnetic powder particles remains, resulting in clear defect indication patterns. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] Patent Publication No. 2004-101193 Summary of the Invention [Problem to be solved by the invention]

[0010] Patent Document 1 describes fluorescent magnetic powder produced by dissolving or dispersing magnetically conductive particles, a fluorescent colorant, and a binder in a solvent to form a paste, drying the resulting paste, and pulverizing the dried material; and fluorescent magnetic powder produced by spray-drying a paste obtained by dispersing magnetically conductive particles, a fluorescent colorant, and a synthetic resin emulsion in water.

[0011] However, if a fluorescent magnetic powder liquid is prepared using fluorescent magnetic powder manufactured by the manufacturing method described in Patent Document 1, the fluorescent pigment on the surface of the magnetic powder particles is likely to peel off or fall off in the fluorescent magnetic powder liquid. Also, during flaw detection testing, the fluorescent pigment on the surface of the magnetic powder particles is likely to peel off or fall off, resulting in a low brightness of the defect indication pattern and a problem of low detection sensitivity due to a background phenomenon that is likely to occur.

[0012] The inventors of the present invention have set the technical objective of solving the above problems, and as a result of numerous trial and error prototypes and experiments, DiameterA fluorescent pigment was prepared by granulating a mixture containing 20% ​​by weight or more and 40% by weight or less of magnetic powder having a particle size of 2 μm or more and 7 μm or less, 5% by weight or more and 12% by weight or less of a resin content of a water-soluble resin-containing emulsion having a glass transition temperature of 10° C. or less, 5% by weight or more and 25% by weight or less of a fluorescent pigment, and water, and dispersing 10% by weight or more and 55% by weight or less of the granulated particles in an aqueous solution containing 5% by weight or more and 35% by weight or less of the resin content of the water-soluble resin-containing emulsion, and then granulating again. In the case of magnetic powder, the fluorescent pigment adheres firmly to the surface of the magnetic powder particles, making it difficult for the fluorescent pigment to peel off or fall off in the fluorescent magnetic powder liquid or during flaw detection testing, and therefore background phenomena are unlikely to occur. Furthermore, a high proportion of the fluorescent pigment remains on the surface of the magnetic powder particles, making it possible to obtain a clear defect indication pattern with a noticeable difference between defective and non-defective areas. This remarkable discovery led to the achievement of the above-mentioned technical objective. [Means for solving the problem]

[0013] The above technical problems can be solved by the present invention as follows.

[0014] The present invention is Diameter The method for producing fluorescent magnetic powder for wet magnetic particle inspection includes granulating a mixture containing 20% ​​by weight or more and 40% by weight or less of magnetic powder having a particle size of 2 μm or more and 7 μm or less, 5% by weight or more and 12% by weight or less of a resin content of a water-soluble resin-containing emulsion having a glass transition temperature of 10° C. or less, 5% by weight or more and 25% by weight or less of a fluorescent pigment, and water, dispersing 10% by weight or more and 55% by weight or less of the granulated particles in an aqueous solution containing 5% by weight or more and 35% by weight or less of the resin content of the water-soluble resin-containing emulsion, and then granulating again to produce fluorescent magnetic powder for wet magnetic particle inspection.

[0015] The present invention also relates to a method for producing fluorescent magnetic powder for wet magnetic particle inspection, wherein the granulation method is spraying in all cases.

[0016] The present invention also relates to a method for producing the magnetic powder, the fluorescent pigment, and the water-soluble resin in the mixture. Resin content of emulsion The present invention relates to a method for producing fluorescent magnetic powder for wet magnetic particle inspection, the method comprising the steps of:

[0017] The present invention also relates to a method for producing fluorescent magnetic powder for wet magnetic particle inspection, in which the particles granulated from the mixture are composite particles in which a fluorescent pigment is attached to a magnetic powder.

[0018] The present invention also relates to a fluorescent magnetic powder liquid for wet magnetic particle inspection, in which the fluorescent magnetic powder produced by the above-mentioned production method is dispersed. Effect of the Invention

[0019] The fluorescent magnetic particles in the present invention are Diameter A mixture containing 20% ​​by weight to 40% by weight of magnetic powder having a particle size of 2 μm to 7 μm, 5% by weight to 12% by weight of a resin content of a water-soluble resin-containing emulsion having a glass transition temperature of 10° C. or less, 5% by weight to 25% by weight of a fluorescent pigment, and water is granulated to produce composite particles in which the fluorescent pigment adheres to the surface of the magnetic powder particles via the water-soluble resin, and then 10% by weight to 55% by weight of the composite particles are dispersed in an aqueous solution containing a water-soluble resin-containing emulsion in which the resin content of the water-soluble resin-containing emulsion is 5% by weight to 35% by weight, and the mixture is granulated again to produce the composite particles, which become fluorescent magnetic powder coated with the water-soluble resin.

[0020] The fluorescent magnetic powder produced by the manufacturing method of the present invention has less fluorescent pigment that peels off or falls off in the fluorescent magnetic powder liquid or during flaw detection testing, making it possible to produce a fluorescent magnetic powder liquid that is less susceptible to the so-called background phenomenon in which peeled-off fluorescent pigment adheres to the surface of the inspected object other than the defective area and emits fluorescence.

[0021] Furthermore, with the fluorescent magnetic powder of the present invention, the amount of fluorescent pigment that peels off or falls off in the fluorescent magnetic powder liquid is small, so a high percentage of the fluorescent pigment remains on the surface of the magnetic powder particles, and when re-sprayed, the fluorescent pigment that has peeled off or fallen off the surface of the magnetic powder particles and the fluorescent pigment that has not adhered to the surface of the magnetic powder particles are dispersed in the water-soluble resin-containing emulsion to coat the surface of the composite particles, resulting in a clear defect indication pattern, and it is possible to prepare a fluorescent magnetic powder liquid with high detection sensitivity that can detect even fine open defects and non-open defects just below the surface.

[0022] In particular, by granulating either method by spraying, fluorescent magnetic powder with a uniform particle size can be produced, making it possible to produce a fluorescent magnetic powder liquid with even higher detection sensitivity that can detect even minute open defects and non-open defects just below the surface.

[0023] Furthermore, if the total solid content of the mixture, which is the magnetic powder, fluorescent pigment, and water-soluble resin, is 65% by weight or less, the mixture becomes suitable for granulation by a spraying method.

[0024] The fluorescent magnetic powder liquid in which the fluorescent magnetic powder of the present invention is dispersed is less likely to cause background phenomena and the fluorescent pigment of the fluorescent magnetic powder remains at a high rate, so that the difference between defective and non-defective areas is significant and a clear defect indication pattern can be obtained, making it a fluorescent magnetic powder liquid that can detect fine open defects and non-open defects just below the surface with high detection sensitivity. [Brief description of the drawings]

[0025] [Figure 1] FIG. 13 is a diagram comparing peeling water. [Diagram 2] FIG. 1 is a diagram showing a method for measuring peel brightness. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0026] The fluorescent magnetic powder in the present invention is produced by granulating composite particles from a slurry-like mixture of magnetic powder, a water-soluble resin-containing emulsion, a fluorescent pigment, and water, and then dispersing the composite particles in an aqueous solution containing the water-soluble resin-containing emulsion and spraying it again, so that the composite particles become fluorescent magnetic powder coated with the water-soluble resin.

[0027] (magnetic powder) The magnetic powder contained in the mixture of the present invention is not particularly limited. Examples of magnetic powders include reduced iron powder, electrolytic iron powder, γ-ferric oxide powder, and iron tetroxide powder.

[0028] The median diameter of the magnetic powder particles is preferably 2 μm to 7 μm, and more preferably 3 μm to 5 μm.

[0029] Median Diameter If the thickness is less than 2 μm, the brightness of the fluorescent magnetic powder liquid may be low, resulting in a decrease in the detection sensitivity of the opening defect portion. If the thickness exceeds 7 μm, the fluorescent magnetic powder liquid may flow, resulting in an unstable magnetic powder pattern.

[0030] The content of the magnetic powder in the mixture is preferably 20% by weight to 40% by weight, and more preferably 30% by weight to 37% by weight.

[0031] If the magnetic powder content is less than 20% by weight, the amount of fluorescent pigment that does not adhere to the surface of the magnetic powder particles increases, making it more likely that a background phenomenon will occur in which the fluorescent pigment adheres to the surface of the test object other than the defective area and emits fluorescence, which may reduce the detection sensitivity of the defective area.

[0032] On the other hand, if the content exceeds 40% by weight, the solid content in the mixture becomes too high, making it difficult to granulate by the spray method.

[0033] (Water-soluble resin-containing emulsion) The mixture in the present invention is an emulsion containing a water-soluble resin having a glass transition temperature of 10° C. or lower.

[0034] If the glass transition temperature exceeds 10° C., the resin will be easily cured, and there is a risk that fine powder of the water-soluble resin will precipitate after spraying.

[0035] The water-soluble resin having a glass transition temperature of 10° C. or less is not particularly limited.

[0036] Examples of the water-soluble resin-containing emulsion in the present invention include an acrylic ester emulsion, a styrene-acrylic emulsion, and a styrene-butadiene emulsion.

[0037] The resin content of the water-soluble resin-containing emulsion contained in the mixture is preferably 5% by weight to 12% by weight, and more preferably 6% by weight to 10% by weight.

[0038] If it is less than 5% by weight, the amount of fluorescent pigment that peels off and falls off from the composite particles increases, making the background phenomenon more likely to occur, and if it is contained in excess of 12% by weight, clumps of the water-soluble resin attached to the fluorescent pigment will form, either of which may reduce the detection sensitivity.

[0039] (Fluorescent pigment) The mixture according to the present invention contains a fluorescent pigment.

[0040] The fluorescent pigment is not particularly limited, but examples thereof include Lumogen Yellow S0790 (manufactured by BASF) and Festa A (manufactured by Swada).

[0041] The content of the fluorescent pigment in the mixture is preferably 5% by weight to 25% by weight, and more preferably 10% by weight to 15% by weight.

[0042] If the content is less than 5% by weight, the brightness of the defect indication pattern will be low, which may result in a decrease in detection sensitivity.

[0043] On the other hand, if the content exceeds 25% by weight, the solid content in the mixture increases, so that the viscosity becomes too high and it becomes difficult to granulate by the spraying method.

[0044] The mixture is preferably in the form of a slurry having a viscosity of 100 cP or less, because this makes it easier to granulate by the spraying method.

[0045] The content of solids in the mixture, consisting of the magnetic powder, the fluorescent pigment, and the water-soluble resin, is preferably 65% ​​by weight or less.

[0046] If the content exceeds 65% by weight, the viscosity becomes too high, making granulation by spraying difficult.

[0047] The mixture can be granulated by spraying it into the air at high temperature in a mist form using a spray dryer to remove water from the droplets and dry them.

[0048] This makes it possible to obtain composite particles in which the fluorescent pigment is adhered to the surface of the magnetic powder particles via the water-soluble resin.

[0049] The fluorescent magnetic powder of the present invention is prepared by dispersing the composite particles in an aqueous solution consisting of water and an emulsion containing a water-soluble resin with a glass transition temperature of 10° C. or less, and then granulating the dispersion again.

[0050] In an aqueous solution containing an emulsion containing water-soluble resin in which composite particles are dispersed, the fluorescent pigment that has peeled off and fallen off from the surface of the magnetic powder particles is dispersed, and if the particles are granulated again, the water-soluble resin in which the fluorescent pigment is dispersed will coat the surface of the composite particles.

[0051] The composite particles to be dispersed in the aqueous solution containing the water-soluble resin-containing emulsion are preferably 10% by weight to 55% by weight, and more preferably 40% by weight to 45% by weight.

[0052] If the content of the composite particles is less than 10% by weight, the surface of the composite particles will be coated with a large amount of water-soluble resin, which may not be sufficiently adsorbed to defective areas. If the content exceeds 55% by weight, the solid content increases, causing the viscosity to become too high, making it difficult to granulate again by the spraying method.

[0053] (Aqueous solution containing a water-soluble resin-containing emulsion) The aqueous solution in which the composite particles are dispersed can be prepared by mixing an emulsion solution containing a water-soluble resin having a glass transition temperature of 10° C. or lower with water.

[0054] If the glass transition temperature exceeds 10° C., the resin will be easily cured, and there is a risk that fine powder of the water-soluble resin will precipitate after spraying.

[0055] The water-soluble resin-containing emulsion having a glass transition temperature of 10° C. or less is not particularly limited, and examples thereof include acrylic ester emulsion, styrene acrylic emulsion, and styrene butadiene emulsion.

[0056] The resin content of the water-soluble resin-containing emulsion in the aqueous solution is preferably 5% by weight to 35% by weight.

[0057] If the proportion of the resin in the aqueous solution is less than 5% by weight, the coating effect is weak, and there is a risk that peeling or falling off of the fluorescent pigment cannot be prevented.

[0058] Moreover, if the content exceeds 35% by weight, the solid content becomes too high, which increases the viscosity, and there is a risk that it will be difficult to granulate by the spraying method.

[0059] (Fluorescent magnetic powder liquid) The prepared fluorescent magnetic powder can be dispersed in an organic solvent such as water or kerosene to produce a fluorescent magnetic powder liquid.

[0060] The amount of fluorescent magnetic powder contained in the fluorescent magnetic powder liquid is preferably 0.3 g / L to 2.0 g / L. This is because minute defects can be detected with high detection sensitivity.

[0061] In order to improve the dispersibility of the fluorescent magnetic powder, a commercially available magnetic powder dispersant for wet magnetic particle inspection may be added to the fluorescent magnetic powder liquid in the present invention.

[0062] (Wet magnetic particle testing method) 1 shows an embodiment of a wet magnetic particle inspection using a fluorescent magnetic powder liquid in which fluorescent magnetic powder is dispersed according to the present invention.

[0063] The object to be inspected is magnetized by the usual axial current method, after which a fluorescent magnetic powder liquid is applied, and the defect indication pattern is observed by irradiating it with an ultraviolet light in a dark place, and the number and size of the defects are measured.

[0064] The fluorescent magnetic powder liquid of the present invention can be suitably used to detect open defects having a width of 0.02 mm or more, and non-open Ketos No. 7 defects just below the surface. EXAMPLES

[0065] The present invention will be described in more detail with reference to examples and comparative examples, but the present invention is not limited thereto.

[0066] As shown in the table, iron oxide powder, an acrylic acid ester emulsion, a melamine-based fluorescent pigment (Shinroihi Color 5005 / manufactured by Shinroihi Co., Ltd.), and water were mixed to prepare a slurry-like mixture.

[0067] The "Water-soluble resin" column in each table indicates the glass transition temperature (Tg) and resin content (wt%) of the acrylic ester resin in the mixture or aqueous solution.

[0068] The mixture thus prepared was sprayed into the air at high temperature using a spray dryer to remove water from the droplets, and then dried and granulated.

[0069] The resulting composite particles were divided into those that were not re-atomized and those that were re-atomized.

[0070] An aqueous solution containing the acrylic ester emulsion was prepared by dissolving the acrylic ester emulsion in water.

[0071] The composite particles to be re-sprayed were dispersed in the prepared aqueous solution containing the acrylic acid ester emulsion, and then granulated again using a spray dryer to obtain re-sprayed fluorescent magnetic powder.

[0072] Hereinafter, those that were not re-sprayed will be referred to as composite particles, and those that were re-sprayed will be referred to as re-sprayed fluorescent magnetic powder.

[0073] (Sprayability) When the re-spraying was possible, the sample was evaluated as ◯ when it could be sprayed with the spray gun, and when it could not be dispersed in the aqueous solution containing the water-soluble resin-containing emulsion and could not be sprayed, the sample was evaluated as x when it could not be dispersed in the aqueous solution containing the water-soluble resin-containing emulsion and could not be sprayed.

[0074] (Detection sensitivity) A type A test piece as specified in JIS Z2320 was attached to a 60 mm square steel material, and while magnetizing it using an axial current method, magnetic powder liquid was applied to it. The detection state of artificial defects in the type A test piece was visually observed and evaluated.

[0075] If the detection sensitivity of the fluorescent magnetic powder liquid in which the re-sprayed fluorescent magnetic powder was dispersed was equal to or greater than the detection sensitivity of the fluorescent magnetic powder liquid in which the composite particles were dispersed, it was evaluated as O, and if it was lower, it was evaluated as X.

[0076] (peel brightness) 0.5 g of each of the re-sprayed fluorescent magnetic powder and composite particles of the Examples and Comparative Examples was dispersed in 1 L of water by adding a dispersant (Ecomagna Dispersant EC-4 / Marktec Co., Ltd.).

[0077] Then, as shown in Figure 2, the water from which the fluorescent magnetic particles had been removed using a magnet (hereinafter referred to as "stripped water") was poured into a transparent Teflon tube with a diameter of 6 mm, and the outer surface of the Teflon tube was irradiated with ultraviolet light, and the emitted light was read by a photosensor.

[0078] In this specification, the brightness of the peeled water read by the photosensor using the above-mentioned method is referred to as peeling brightness.

[0079] The peeling brightness of the composite particles before re-spraying in Example 1 was 0.714, and the peeling brightness of the re-sprayed fluorescent magnetic powder after re-spraying was 0.155 (FIG. 1).

[0080] The reduction rate of peeling brightness was calculated using the following formula. (Formula) 0.155 / 0.714×100=21.7%

[0081] Similarly, re-sprayed fluorescent magnetic powder whose peeling brightness decreased by 50% or less compared to the peeling water of the fluorescent magnetic powder liquid in which the composite particles were dispersed before re-spraying was evaluated as O, and those whose peeling brightness decreased by more than 50% were evaluated as X.

[0082] The results are shown in Tables 1 and 2. In the table, "resin precipitation" indicates that fine powder of water-soluble resin was generated after spraying.

[0083] A comparison of the stripping water from composite particles and re-sprayed fluorescent magnetic particles is shown in Figure 1.

[0084] [Table 1]

[0085] [Table 2] [Table 3]

[0086] As shown in Tables 1 to 3, the re-sprayed fluorescent magnetic powder of the present invention is unlikely to peel off or fall off even when dispersed in water, demonstrating that a fluorescent magnetic powder liquid in which background phenomena are unlikely to occur can be prepared.

[0087] Therefore, it was proven that the fluorescent magnetic powder liquid in which the fluorescent magnetic powder of the present invention is dispersed can provide a clear defect indication pattern and is a fluorescent magnetic powder liquid with high detection sensitivity. [Industrial Applicability]

[0088] The fluorescent magnetic powder of the present invention is a fluorescent magnetic powder in which composite particles, in which a fluorescent pigment is attached to the surface of magnetic powder particles via a water-soluble resin, are further coated with a water-soluble resin. Since the fluorescent pigment is firmly attached to the surface of the magnetic powder particles, the fluorescent pigment is unlikely to peel off or fall off in the fluorescent magnetic powder liquid or during flaw detection testing, and therefore a fluorescent magnetic powder liquid in which background phenomena are unlikely to occur can be prepared. In addition, since there is little peeling or falling off of the fluorescent pigment, a large proportion of the fluorescent pigment remains on the surface of the magnetic powder particles. Moreover, the fluorescent pigment that peels off or falls off during the production of the composite particles is dispersed in an aqueous solution containing an emulsion containing a water-soluble resin, and when the particles are sprayed again, the water-soluble resin in which the peeled fluorescent pigment is dispersed coats the surface, making it possible to produce a fluorescent magnetic powder liquid that can produce a clear defect indication pattern. Therefore, the fluorescent magnetic powder liquid in which the fluorescent magnetic powder of the present invention is dispersed can detect minute open defects and non-open defects immediately below the surface with high detection sensitivity. Therefore, the present invention has high industrial applicability.

Claims

1. A method for producing fluorescent magnetic powder for wet magnetic particle inspection testing, comprising: granulating a mixture containing 20% ​​by weight or more and 40% by weight or less of magnetic powder having a median diameter of 2 μm or more and 7 μm or less, 5% by weight or more and 12% by weight or less of a resin content of a water-soluble resin-containing emulsion having a glass transition temperature of 10° C. or less, 5% by weight or more and 25% by weight or less of a fluorescent pigment, and water; dispersing 10% by weight or more and 55% by weight or less of the granulated particles in an aqueous solution containing 5% by weight or more and 35% by weight or less of the resin content of the water-soluble resin-containing emulsion, and then granulating again to produce fluorescent magnetic powder.

2. 2. The method for producing fluorescent magnetic powder for wet magnetic particle inspection according to claim 1, wherein said granulation method is spraying.

3. 3. The method for producing fluorescent magnetic powder for wet magnetic particle inspection according to claim 1, wherein the solid content of said mixture consisting of said magnetic powder, said fluorescent pigment and the resin content of said water-soluble resin-containing emulsion is 65% by weight or less.

4. 4. The method for producing a fluorescent magnetic powder for wet magnetic particle testing according to claim 1, wherein the particles granulated from the mixture are composite particles in which a fluorescent pigment is attached to the surface of magnetic powder particles.

5. 5. A fluorescent magnetic powder liquid for wet magnetic particle inspection, comprising a fluorescent magnetic powder produced by the method according to claim 1 dispersed therein.

Citation Information

Patent Citations

  • Colored magnetic powder for magnetic powder inspection, and manufacture thereof

    JP1995244020A

  • Magnetic particle compound for wet magnetic particle testing

    JP2002031620A

  • Fluorescent magnetic particle for magnetic particle test

    JP2004101193A

  • Fluorescent magnetic powder for wet magnetic powder flaw detection test and wet magnetic powder flaw detection method using the same

    JP2018173290A

  • Method using aqueous emulsion having magnetizable particles for detecting flaws in magnetizable workpieces

    US4361806A